2008 International Conference on Computational Sciences and Its Applications 2008
DOI: 10.1109/iccsa.2008.43
|View full text |Cite
|
Sign up to set email alerts
|

Design of a High-Accuracy Classifier Based on Fisher Discriminant Analysis: Application to Computer-Aided Diagnosis of Microcalcifications

Abstract: In this paper we present a high accuracy computer-aided diagnosis scheme. The goal of the developed system is to classify benign and malignant microcalcifications on mammograms. It is mainly based on a combination of wavelet decomposition, feature extraction and classification methodology using Fisher's linear discriminant. The contribution of wavelet decomposition is to denoise and to enhance regions of interests (ROI) containing abnormalities. Feature extraction is performed using spatial grey level dependen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Hence, many researchers have contributed in the development and the growth of CAD systems. The researchers who have explored the area to distinguish malignant and benign microcalcifications have either used only the texture features [10][11][12][13][14][15][16][17], or a combination of texture and shape features [4,[18][19][20]. For extracting the shape-based features, some researchers have worked to extract shape and topology of individual microcalcifications [21,22].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, many researchers have contributed in the development and the growth of CAD systems. The researchers who have explored the area to distinguish malignant and benign microcalcifications have either used only the texture features [10][11][12][13][14][15][16][17], or a combination of texture and shape features [4,[18][19][20]. For extracting the shape-based features, some researchers have worked to extract shape and topology of individual microcalcifications [21,22].…”
Section: Literature Reviewmentioning
confidence: 99%
“…To distinguish benign and malignant microcalcifications, various researchers have proposed different approaches to compute texture features extracted from a region that contains microcalcifications. The most commonly used texture features are GLCM-based texture features [10,13,19], SGLD-based texture features [11], GLRLMbased texture features [10], LBP-based texture features [15], Gabor texture features [9,14] and wavelet-based texture features [19,20].…”
Section: 3bmentioning
confidence: 99%
“…The underlying principle of preprocessing is to enlarge the intensity difference between objects and background and to produce reliable representations of breast tissue structures. More details of the proposed preprocessing method can be found in [17,18].…”
Section: Frameworkmentioning
confidence: 99%
“…al [7] combined shape, spectral, and GLCM features to classify microcalcifications using kernelbased support vector machine classifiers. Hamdi et al [8] classified MC clusters from MIAS database using GLCM and spectral features, feature selection using Fisher discriminate analysis (FDA), and a KNN classifier. Other studies [9], [10] demonstrated that it is not the texture of MCs objects but it the texture of breast tissue surrounding microcalcifications that can be useful for cancer diagnosis.…”
mentioning
confidence: 99%